Pharmacotherapy for methamphetamine/amphetamine use disorder—a systematic review and meta‐analysis. (12th September 2019) - Chan, Brian; Freeman, Michele; Kondo, Karli; Ayers, Chelsea; Montgomery, Jessica; Paynter, Robin; Kansagara, Devan
Abstract: Aims: Addiction to methamphetamine/amphetamine (MA/A) is a major public health problem. Currently there are no pharmacotherapies for MA/A use disorder that have been approved for use by the US Food and Drug Administration or the European Medicines Agency. We reviewed the effectiveness of pharmacotherapy for MA/A use disorder to assess the quality, publication bias and overall strength of the evidence. Methods: Systematic review and meta‐analysis. We searched multiple data sources (MEDLINE, PsycINFO and Cochrane Library) to April 2019 for systematic reviews (SRs) and randomized controlled trials (RCTs). Included studies recruited adults who had MA/A use disorder; sample sizes ranged from 19 to 229 participants. Outcomes of interest were abstinence, defined as 3 or more consecutive weeks with negative urine drug screens (UDS); overall use, analyzed as the proportion of MA/A negative UDS specimens; and treatment retention. One SR of pharmacotherapies for MA/A use disorder and 17 additional RCTs met our inclusion criteria encompassing 17 different drugs (antidepressants, antipsychotics, psychostimulants, anticonvulsants and opioid antagonists). We combined the findings of trials with comparable interventions and outcome measures in random‐effects meta‐analyses. We assessed quality, publication bias and the strength of evidence for each outcome using standardized criteria. Results: There was low‐strength evidence from two RCTs that methylphenidate may reduce MA/A use: 6.5 versus 2.8% MA/A‐negative UDS in one study ( n = 34, P = 0.008) and 23 versus 16% in another study ( n = 54, P = 0.047). Antidepressants as a class had no statistically significant effect on abstinence or retention on the basis of moderate strength evidence. Studies of anticonvulsants, antipsychotics (aripiprazole), opioid antagonists (naltrexone), varenicline and atomoxetine provided either low‐strength or insufficient evidence of no effect on the outcomes of interest. Many of the studies had high or unclear risk of bias. Conclusions: On the basis of low‐ to moderate‐strength evidence, most medications evaluated for methamphetamine/amphetamine use disorder have not shown a statistically significant benefit. However, there is low‐strength evidence that methylphenidate may reduce use.